Keterampilan Pengolahan Produk Diversifikasi Hasil Perikanan Bagi Masyarakat Desa Sungai Rengas Kabupaten Kubu Raya - Vatria, Belvi; Riyadhi, Baidhillah; Kusumawati, Rr. Puji Hastuti; Primadini, Vivin (Politeknik Negeri Pontianak, 2024)
Sungai Rengas Village, Kubu Raya Regency is on the banks of the Kapuas River, which is the longest and widest river in West Kalimantan Province. Apart from that, in the village there is a Coastal Fishing Port which is very active in fish loading and unloading activities. Sungai Rengas Village has great potential to develop the fisheries sector, especially the diversified fishery product processing sub-sector. However, the skills of the people of Sungai Rengas village in processing diversified fishery products are still minimal. Therefore, to utilize the existing fisheries potential, it is necessary to carry out community service activities regarding processing skills for diversified fishery products for the community in the village. Diversification of fishery product processing is a technique for processing fishery products by applying appropriate technology between fish meat and other additives to obtain added value to fishery products or accommodate excess harvest. The target audience for this community service activity is housewives and young women who live in Sungai Rengas Village with the consideration that the role of housewives and young women is very necessary in helping to improve nutrition and family income. The aim of this community service activity is to increase knowledge and skills in processing diversified fishery products for the people of Sungai Rengas Village. The implementation method is training in processing diversified fishery products using good manufacturing practice standards. This activity ran smoothly and was completed and was attended by 15 training participants. The Sungai Rengas Village Government, Kubu Raya Regency, strongly supports this activity and hopes it can be sustainable.